Здобутки інклюзивної освіти дорослих у Мексиці - Жижко, Олена (Studies in Comparative Education, 2014)
В статті представлено результати науково-педагогічного дослідження, метою якого був аналіз здобутків інклюзивної освіти дорослих у Мексиці. Автором встановлено, що інклюзивність програм мексиканської системи освіти дорослих виражається у розробці спеціальних курсів для дорослих з фізичними і розумовими вадами, емігрантів, представників етнічних меншин та інших категорій дорослого населення. В статье представлены результаты научно-педагогического исследования, целью которого был анализ достижений инклюзивного образования взрослых в Мексике. Автором выявлено, что инклюзивность программ мексиканской системы образования взрослых выражается в разработке специальных курсов для взрослых с физическими и умственными недостатками, эмигрантов, представителей этнических меньшинств и других категорий взрослого населения. This article presents the results of scientific pedagogical research that aims was to analyze the achievements of inclusive education of adults in Mexico. The author found that in Mexico the problems of adult education studied F. Adam, A. Alcala, P. Casau, P. Latapi Sarre, R. Ludojoskiy, L. Rodriguez, J. Fermin Gonzalez et al. Since the late 90s of the twentieth century, the Government of Mexico with the support of the public, private and civil society organizations developed such innovative inclusive program of adult education : «Education Model for Life and Work», training projects for blind and visually impaired, «Bilingual Integrated Indians», «Bilingual Indians with knowledge of the Spanish as second language», program for Mexicans living abroad, «Training for the work of the third age adults», «Learning of temporary agricultural migrant workers» and others. «Model of Education for Life and Work» (MEVIT) is an innovative national educational program for youth and adults who are in conditions of social and economic marginality, based on the needs and interests of this community: the acquisition of knowledge for accreditation of basic education, and knowledge and skills in various areas of everyday life and work. Theoretical and methodological basis of the MEVIT´s program is socio-pedagogical paradigm, according to which the training needs caused by the basic needs of an adult. The concept of adult education programs based on the ideas of constructivism and cognositivism and postulates that education should meet the basic human needs and improve self-esteem, freedom, national identity and multiculturalism, develop cognitive abilities and more. In addition to the general curriculum, designed for any category of adult, MEVIT developed special offers for those segments of the population of Mexico as adults with physical and mental disabilities, HIV-infected, immigrants, ethnic minorities and others. Each group provides by a special curriculum to meet the needs of its members. One of the MEVIT´s training projects for disabled adapt the program for blind and visually impaired using Braille and audio materials. This project, which started at the initiative of the National Institute of Adult Education and NGOs engaged in education of blind and visually impaired people, using printed material developed by MEVIT for creating of typing interactive software and audio text books and other teaching materials reproduced on computers of «public spaces». Another inclusive MEVIT´s project is the development of two training programs for Indians: «Bilingual Integrated Indians» and «Bilingual Indians with knowledge of Spanish as a second language». The aim of this project is to provide basic and vocational training to representatives of many ethnic groups of Mexico in their native languages using educational material connected with their social and cultural life, and to teach the Spanish language, keeping knowledge of their own dialects and cultural identity. So, the inclusive character of Mexican programs of adult education is reflected in the development of special courses for the adults with physical and mental disabilities, immigrants, ethnic minorities and other categories of adults.